2019
DOI: 10.1002/jnr.24515
|View full text |Cite
|
Sign up to set email alerts
|

The role of TLR4 and HO‐1 in neuroinflammation after subarachnoid hemorrhage

Abstract: This review on the mechanisms of neuroinflammation following subarachnoid hemorrhage will focus mainly on toll‐like receptor 4 (TLR4), Heme Oxygenase‐1 (HO‐1), and the role of microglia and macrophages in this process. Vasospasm has long been the focus of research in SAH; however, clinical trials have shown that amelioration of vasospasm does not lead to an improved clinical outcome. This necessitates the need for novel avenues of research. Our work has demonstrated that microglial TLR4 and microglial HO‐1, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 96 publications
0
32
0
Order By: Relevance
“…Activation of TLR4 has been shown to trigger and modulate neuroinflammatory responses and contribute to secondary brain injury after both acute and chronic neurological diseases [ 32 ]. Previous studies using the mouse SAH model showed that activation of TLR4 promoted neuronal apoptosis via microglial- and MyD88-dependent mechanism in the early phase of SAH, whereas the toll receptor-associated activator of interferon (TRIF)-dependent but microglia-independent mechanism was involved in the late phase [ 33 ]. In the present study, the increased expression of TLR4 and MyD88 was detected by western blot after SAH, which was further enhanced by sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TLR4 has been shown to trigger and modulate neuroinflammatory responses and contribute to secondary brain injury after both acute and chronic neurological diseases [ 32 ]. Previous studies using the mouse SAH model showed that activation of TLR4 promoted neuronal apoptosis via microglial- and MyD88-dependent mechanism in the early phase of SAH, whereas the toll receptor-associated activator of interferon (TRIF)-dependent but microglia-independent mechanism was involved in the late phase [ 33 ]. In the present study, the increased expression of TLR4 and MyD88 was detected by western blot after SAH, which was further enhanced by sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, hemorrhagic strokes are caused by a ruptured artery or vessel that subsequently enables RBCs to enter the brain, leading to oxidative stress. When looking specifically at a hemorrhagic stroke, free heme- and hemoglobin (Hb)-induced neuroinflammation and cell death been have shown to worsen patient outcomes and exacerbate symptoms the longer they are left untreated [ 14 ]. One potential theory to improve outcomes is to reduce free-circulating RBCs, the haptoglobin and hemoglobin (Hp–Hb) complex, and the heme–hemopexin complex, which, respectively, bind to CD36, CD163, and LRP1 [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heme acts as a potent activator of TLR4 as well as the MyD88 and TRIF cascades that lead to neuroinflammation [ 204 ]. This effect may be mediated through the activation of heme oxygenase-1, an enzyme that catalyzes the degradation of heme [ 223 ]. While the activation of the TLR4-MyD88 cascade is mandatory for tissue injury and vasospasm in the early stage of SAH, tissue injury and vasospasm in the late phase of SAH are mediated through the TLR4-TRIF pathway [ 99 ].…”
Section: The Role Of Toll-like Receptors In Cvdsmentioning
confidence: 99%